Distribution and nest occupancy patterns of Oecophylla smaragdina (hymenoptera: formicidae) colonies in Southeast Asian oil palm plantations - Exélis, Moïse Pierre; Ramli, Rosli; Idris, Azarae; Ibrahim, Rabha W.; Clemente-Orta, Gemma Maria; Ayra-Pardo, Camilo; Abdullah Sani, Muhamad Shirwan (Elsevier, 2025)
The Asian weaver ant (Oecophylla smaragdina F.) is an effective natural predator of key pests affecting economically important crops across Southeast Asia. This study presents a large-scale assessment of its spatial distribution in oil palm plantations (200,000 ha surveys). Geographic coordinates and colony-level data were recorded to investigate spatial structure, the occupation pattern, nesting behaviour, and typology. To distinguish functional nest types (brood versus barracks), 26 samples were analysed using discriminant analysis (DA). The vertical positioning within the palm canopy emerged as a reliable visual indicator (nest morphology, internal content proved insufficient). Brood nests were located at heights averaging 8.0 ± 1.3 m (barracks ± 4.0 m). Colonies exhibited polydomous structure, forming irregular, interconnected spatial patches, with the first documented cases of monodomy observed in shorter palms. The antagonist ant species Odontoponera denticulata is suggested as a potential disruptor vector. Colony age, estimated from the number of nests and occupied palms, was modelled using negative binomial and Poisson distribution. Mature colonies occupied 10–12 palms within an area of 800–2500 m2, separated by consistent ant-free buffer zones (∼20 m2). Colonisation progressed gradually, with colonies occupying an average of 3–4 palms per year, reaching maturity within 3–4 years. Poisson modelling predictive estimation of colony age based on nesting parameters shows a strong correlation. O. smaragdina colonies’ widespread, stable presence throughout oil palm landscapes underscores the species’ potential as a sustainable biological control agent against the invasive bagworm Metisa plana Walker (Lepidoptera: Psychidae), a major threat to oil palm yields.